Involvement of SRF coactivator MKL2 in BDNF‐mediated activation of the synaptic activity‐responsive element in the Arc gene. Issue 2 (12th November 2018) - Kikuchi, Keietsu; Ihara, Daisuke; Fukuchi, Mamoru; Tanabe, Hiroki; Ishibashi, Yuta; Tsujii, Junya; Tsuda, Masaaki; Kaneda, Marisa; Sakagami, Hiroyuki; Okuno, Hiroyuki; Bito, Haruhiko; Yamazaki, Yuya; et al.
Abstract: The expression of immediate early genes (IEGs) is thought to be an essential molecular basis of neuronal plasticity for higher brain function. Many IEGs contain serum response element in their transcriptional regulatory regions and their expression is controlled by serum response factor (SRF). SRF is known to play a role in concert with transcriptional cofactors. However, little is known about how SRF cofactors regulate IEG expression during the process of neuronal plasticity. We hypothesized that one of the SRF‐regulated neuronal IEGs, activity‐regulated cytoskeleton‐associated protein ( Arc ; also termed Arg3.1 ), is regulated by an SRF coactivator, megakaryoblastic leukemia (MKL). To test this hypothesis, we initially investigated which binding site of the transcription factor or SRF cofactor contributes to brain‐derived neurotrophic factor (BDNF)‐induced Arc gene transcription in cultured cortical neurons using transfection and reporter assays. We found that BDNF caused robust induction of Arc gene transcription through a cAMP response element, binding site of myocyte enhancer factor 2, and binding site of SRF in an Arc enhancer, the synaptic activity‐responsive element (SARE). Regardless of the requirement for the SRF‐binding site, the binding site of a ternary complex factor, another SRF cofactor, did not affect BDNF‐mediated Arc gene transcription. In contrast, chromatin immunoprecipitation revealed occupation of MKL at the SARE. Furthermore, knockdown of MKL2, but not MKL1, significantly decreased BDNF‐mediated activation of the SARE. Taken together, these findings suggest a novel mechanism by which MKL2 controls the Arc SARE in response to BDNF stimulation. Abstract : The activity‐regulated cytoskeleton‐associated protein ( Arc ) gene is a serum response factor (SRF) target, but little is known about its transcriptional regulation by SRF cofactors. Here, we demonstrate that SRF cofactor megakaryoblastic leukemia 2 (MKL2) binds to the Arc gene enhancer, a synaptic activity‐responsive element (SARE), and mediates brain‐derived neurotrophic factor (BDNF)‐induced Arc SARE activation.